(untitled) (Jóvenes en la Ciencia, 2025)
This article aims to analyze the historical and functional evolution of the Medical Network of the University of Guanajuato, a healthcare system established in 1996 to provide direct and high-quality medical care to university employees and their beneficiaries. Through a qualitative, descriptive, and historical approach, a documentary review is conducted to understand the reasons behind its creation, its main administrative and technological milestones, and its advantages over traditional healthcare models such as the ISSSTE. The research highlights how the UG Medical Network has managed to establish an efficient service adapted to the needs of its community by incorporating innovation and promoting the integral health of its beneficiaries. Likewise, current challenges are identified, such as financial sustainability and geographic coverage, along with opportunities to strengthen and expand this model. In addition, challenges and opportunities are identified to reinforce this model which, despite its limitations, clearly exemplifies how a public university can promote the well-being of its staff through its own healthcare system. This analysis seeks to provide a foundation aimed at renewing and optimizing university medical care, reaffirming the institutional commitment to quality and warmth in health services for its community.